Firm innovation activities and consumer brand loyalty: A path to business sustainability in Asia - Yi, Lin; Khan, Muhammad Saqib; Safeer, Asif Ali (Frontiers in Psychology, 2022)
Background: In recent years, technological advancements have increased the importance of innovation activities. Therefore, firms invest millions of dollars in innovation activities to ensure long-term business sustainability. Similarly, consumer concerns have increased dramatically over the past years. Thus, brand loyalty has become a top priority for firms and consumers. In this background, this research examines how firms' innovation activities translate into consumer brand loyalty to assure business sustainability in Asian markets, particularly China, Pakistan, and Indonesia. Objectives: This study's specific objectives are to comprehend the concept of firms' innovation activities and their effect on the brand prototype. Examine the effect of the brand prototype on global brand preference, recommendation, and loyalty among Asian consumers. Find out the impact of brand preference on brand recommendations and the influence of brand recommendations on brand loyalty among Asian consumers. Methods: A total of 814 consumers from Asian countries (China, Pakistan, and Indonesia) participated in this study, and structural equation modeling was used to analyze the data. Results: The findings indicate that firms' innovation activities, such as processes, products, and store environment, positively influenced the brand prototype, thereby increasing consumer brand knowledge. Likewise, brand prototype contributes to developing brand preference, brand recommendation, and brand loyalty among Asian consumers. Lastly, consumer brand preference significantly influenced brand recommendation, which positively improves consumer brand loyalty in Asia. Conclusion: This study concluded that Asian (Chinese, Pakistani, and Indonesian) consumers have favorable perceptions of firms' innovation activities (i.e., process, product, and store environment innovation), which influences their ability to develop brand prototypes to increase consumer brand knowledge. Similarly, brand prototype fosters brand preference, recommendation, and loyalty. Likewise, favorable brand preference encourages consumers to recommend the brand to others, strengthening brand loyalty. Thus, firms should invest in innovation activities to strengthen consumer brand loyalty in Asian markets. Consequently, this study may assist multinational corporations in increasing their business volumes and market shares in Asia. Managerial Recommendations: This study provides important managerial recommendations. The findings revealed that global managers can develop and implement several branding strategies for sustaining their businesses in the Asian environment.